A Rare Presentation of Stage IV Large Cell Neuroendocrine Carcinoma of the Cervix with Metastasis to the Cranium - Neema Hooker; Sveta Mohanan; R. Tucker Burks (Case Reports in Obstetrics and Gynecology)
Neuroendocrine tumors (NETs) are aggressive diseases developing from neuroendocrine cells that most frequently involve the gastro-entero-pancreatic tract and the lung, but more rarely are found in almost all body tissues. Limited biological and clinical data are currently available for NETs in uncommon sites, such as female genital tract. NETs represent 0.9% to 1.5% of the tumors of the uterine cervix. This case is reported on a 75-year-old Caucasian woman, presenting with dental and generalized pain for two weeks. Later during her admission, facial droop and diplopia were noticed. Radiological findings ruled out cerebrovascular accident but revealed multiple bone marrow lesions involving the left and the right clivus, right Meckel's cave, and posterior margin of the right cavernous sinus. Findings also included pulmonary nodules and adenopathy supporting diagnosis of likely stage IV metastatic carcinoma. Further imaging revealed homogeneous enhancement of the uterus suggestive of diffusely infiltrative carcinoma; pathology results confirmed large cell neuroendocrine carcinoma of the uterine cervix (LCNEC) giving her a 1.5-month median survival range.